The Relationship Between Mother Visit to Maternal and Child Health Centre (MCHC) and Timely of Giving Complementary Foods in Timur Tengah Selatan Regency, Nusa Tenggara Timur Province - Wenny Ino Ischak (Health Notions, 2019)
The introduction of feasible complementary foods at 6 months together with continued breastfeeding up to two years of age or beyond. is very important to infant. This study aimed to assess factors associated with the accuracy of the age of supplementary feeding to infant. This study used a cross-sectional design of community-based and carried out in nine districts in the Timur Tengah Selatan Regency,Nusa Tenggara Timur province. It was conducted of the month, October to December 2013 in 9 sub-districts selected. The research subjects were children aged 6-23 months (n = 3578). Data were collected by trained local personnel using a standardized questionnaire. This study showed that there is 77.4% of the respondents have given complementary feeding at suggested time (6 mounths). Type supplementary food given was 56.5% in the form of instant porridge. Giving of complementary foods at 6 months as recommended midwife was 34.6% whereas the reason that it was time to give complementary food before the age of 6 months was only 7.9%. it was found statistically significant where the correlation between giving complementary foods and regularly bring the child to the IHC was 93.7% (P = 0:02), while its relationship with the child's diet counseling ever got was 78.5% (P = 0.00). Keywords: complementary foods; integrated health care; children 6-24 mounths of age